Universities as Embedded Knowledge Hubs and the Challenge of Local Development. The US Lessons and the Italian Case - Ciapetti, Lorenzo (European Spatial Research and Policy, 2010)
This article discusses the claim of a new paradigm in the knowledge production and diffusion process, and the need to assess the regional and local implications of this modal shift. After introductory remarks included in the first part of the paper, its next section introduces the theme of localisation of knowledge as a source of regional development; section three examines the lessons we can extract from the US university system (with a particular regard to the case of Johns Hopkins University and the recent project for a biotech park in the city of Baltimore); in section four an illustration of the Italian University system leads to a description of the current evolution of the University of Bologna toward a new entrepreneurial role. The last part of the paper discusses the embedded role of universities in the light of the two cases presented in the previous sections and draws the conclusions in terms of regional policy.